Historia Popular dos Papas - Chantrel, J. (Livraria Editora de Texixeria de Fretas, 1877)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬.; 18.Bookworm; 2.Damage

Historia Popular dos Papas - Chantrel, J. (Livraria Editora de Texixeria de Fretas, 1877)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬.; 18.Bookworm; 2.Damage

Historia Popular dos Papas - Chantrel, J. (Livraria Editora de Texixeria de Fretas, 1879)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬.; 18.Bookworm; 2.Damage